OBSERVATION ON THE FOOD AND FEEDING HABITS OF SOME FLATFISHES OF ORISSA COAST - Datta, N C; Das, M (Indian Journal of Fisheries, 2011)
The Cynogiossids, Cynoglossus arel, C. lingua, C. biljneatus and Paraplaguisa blochii, are purely carnivorous iii nature, their food comprising mainly polychaetes, crustaceans and molluscs. A remarkable shift in their feeding habit with the increase of body length is observed from the index of preponderance of different food items. While fishes of smaller body length prey mainly upon the amphipods, the larger ones mainly feed upon other crustaceans. Seasonal variation of different food items has also been observed.